Strategi Pemberdayaan Masyarakat Mewujudkan Kemandirian Ekonomi dan Menurunkan Angka Stunting Melalui Budidaya Aquaponik Dalam Mendorong Pencapaian Target SDGs - Yunginger, Raghel; Arifin, Sri Sutarni (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2024)
The community service program through the Village-Development Thematic Community Service Program for Gorontalo State University students is synergized with the Village SDGs program such as in Hutadaa Village. Based on the typology of the Village SDGs, Hutadaa Village has a village typology without poverty and a village typology caring for health. This village typology shows the condition of villages that must receive economic and health strengthening interventions, especially the handling of the stunting problem which is still confirmed in Hutadaa Village, Gorontalo Regency. Therefore, the form of student service at UNG is through the Thematic Community Service Program in Developing Village which is focused on community empowerment strategies in realizing family economic independence and simultaneously suppressing the stunting rate in this village. One of the empowerment efforts for communities or families whose children suffer from stunting is through aquaponics cultivation which is an integrated cultivation system between fisheries and agriculture. The results of this KKN student activity have given birth to three groups of aquaponic cultivation managers consisting of two groups from families of stunting sufferers and one group from youth youth organizations in Hutadaa Village. Aquaponic cultivation is expected to be a source of family nutritional intake as well as a source of family income to support the family with nutritious food. To encourage the sustainability of the aquaponic cultivation program consistently, this service activity is continued with assistance from the village which is included in the village RPJM and also becomes a sustainable program from UNG for student service activities for KKN UNG students in the next period.